Naturalność religii a istnienie niewiary - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2011)
Sławomir Sztajer – THE NATURALNESS OF RELIGION AND THE EXISTENCE OF UNBELIEF This article discusses the ‘naturalness of religion’ hypothesis formulated by some repre-sentatives of the cognitive science of religion, and its consequences for understanding theism and atheism. The hypothesis states, that religious beliefs are natural in the sense that they are a result of ordinary cognitive processes, and as such depend on noncultural constraints. According to this view, beliefs in supernatural agents are relatively more natural than unbelief. This, however, seems to contradict the fact, that there are many atheists, agnostics, and religiously indifferent people. The author tries to answer the question whether atheism poses any problem for the naturalness of religion hypothesis, and if yes, whether this problem can be solved. He points out that there is not one but many answers to that question within the cognitive science of religion. The natural-ness of religion does not preclude the existence of unbelief, but it makes unbelief more cognitive-ly costly than belief in deities.